Diagnosis and Treatment of Chronic Viral Hepatitis B and D - Makhmatkulova G. M; Rakhmonova M.Sh; Karamatullaeva Z.E (Genius Journals, 2023)
Hepatitis is an acute and chronic liver disease of a diffuse inflammatory nature. Violation may be due to various factors. Over the past few years, this disease has begun to be recorded frequently among diseases of the gastrointestinal tract. Regardless of the type of introduction of the virus into the patient’s body, in which a violation and defect of the liver parenchyma is noted. Hepatitis B and D viruses are considered a more common factor in chronic hepatitis, liver cirrhosis and hepatocellular carcinoma. Currently, clinical testing of interferon inducers of artificial and natural origin, which are used in practical healthcare, is being carried out. Some of them are used to prevent and cure viral hepatitis.
Keywords: Interferons; recombinant; beroferon; intron